The contribution of Abdul Raouf Al-Sinkaili (d.1693) to Astronomy and Calender (the Study of Philology of book entitled "Risalah fi at-Taqwim" - Arwin Juli Rakhmadi; Masykur Syafruddin; Akrim Akrim (IJISH (International Journal of Islamic Studies and Humanities), 2022)
This study aimed to identify the biography of Sheikh Abdul Raouf Al-Sinkili and his contribution to astronomy through his book "Risalah fi at-Taqwim”. This study applies qualitative research, which focuses on scientific biography. The data was obtained by analysing the content, which was conducted in three steps: (1) preparing the research, (2) preparing the manuscript “Risala fi at-taqwim” by Syeikh Abdul Raouf Al-Sankaili which is related to the research, and (3) analysing the manuscripts, including biographies of the author, astronomical developments, and the content analysis investigation. By analysing the manuscript’s contents, this research produces an overview and the contribution of Sheikh Abdul Raouf Al-Sinkaili to astronomy, especially in the calendar field.